EVOLVING OF ACCURATE ONLINE PURCHASING MODULE TO IMPROVE STUDENTS' LEARNING OUTCOMES - Panjawiyati, Tika; Astuti, Elly; Yusdita, Elana Era (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT The objectives of this research are (1) the procedure for developing an Accurate Online purchasing module, (2) the quality level of the Accurate Online purchasing module, and (3) the level of effectiveness of the Accurate Online purchasing module. The method used for research and development is Accurate Online Borg & Gall procedure, which is modified into seven stages. The subjects in this research were Accounting Education students at the Universitas PGRI Madiun. Data collection techniques are observation, interview, questionnaires, documentation, and test results. Data processing is done using SPSS. The primary product field test uses a nonequivalent control group design. Student learning test results were analyzed using the Mann-Whitney test. The results of this research indicate that the scientific-based Accurate Online purchasing module that has been developed is declared valid, practical, and effective in improving student learning outcomes. ABSTRAK Tujuan penelitian ini adalah (1) prosedur pengembangan modul pembelian Accurate Online, (2) tingkat kualitas modul pembelian Accurate Online, dan (3) tingkat efektivitas modul pembelian Accurate Online. Metode penelitian dan pengembangan yang digunakan sesuai dengan prosedur Borg & Gall yang dimodifikasi menjadi tujuh tahap. Subyek dalam penelitian ini adalah mahasiswa Pendidikan Akuntansi Universitas PGRI Madiun. Teknik pengumpulan datanya adalah observasi, wawancara, angket, dokumentasi, dan hasil tes. Pengolahan data dilakukan dengan menggunakan SPSS. Uji lapangan produk utama menggunakan desain kelompok kontrol nonekuivalen. Analisis tes hasil belajar siswa dianalisis dengan menggunakan uji Mann-Whitney. Hasil penelitian menunjukkan bahwa modul pembelian Accurate Online berbasis saintifik yang dikembangkan dinyatakan valid, praktis, dan efektif dalam meningkatkan hasil belajar siswa.